Centenary Rural Development Bank, Uganda: A Flagship of Rural Bank Reform in Africa - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2003)
Centenary RDB is a commercial bank that provides deposit, credit and money transfer services indiscriminately to men and women of lower income. By insisting on loan recovery and cost coverage, it has reached more men and women in rural areas than any other institution in Uganda. With minimum deposits of 6 and minimum loans of 30, access barriers are low. 11 of its 16 branches, 73% of its deposits and 82% of its loans are in rural areas. Established by the Catholic Church of Uganda as a trust fund in 1983, it developed a strength in savings mobilization but performed poorly as a financial intermediary. In 1990, the political will to reform the fund evolved in the board, resulting in the fund's transformation into a commercial bank in 1993. With support from various donors including the German Savings Banks Foundation, the bank evolved into the most successful financial intermediary in Uganda. This has made the bank the African flagship of rural and agricultural banking, combining sustainability with outreach to the rural poor and demonstrating the feasibility of agricultural lending. With equity capital of 6.8m and total assets of 49.85m as of December 2001, it has mobilized 39.9m from 280,00 depositors, provided 14m in loans outstanding to 22,000 small borrowers, earned returns of 4% on average assets and 28% on equity, and, since 1999, finances its expansion from its profits. Centenary RDB has several stories to tell: - one about the feasibility and impact of rural and agricultural bank reform - addressed to the community of agricultural development banks (AgDBs) in Africa and those who decide on their fate; - another one about the compatibility of institutional sustainability and outreach to both men and women in rural areas - addressed to the community of microfinance institutions (MFIs) and their donors; - a third one about the feasibility of agricultural lending to men and women - best told by the staff and clients at Mbale branch and addressed to financial institutions weary of risky agricultural lending.
Older version: http://hdl.handle.net/10419/30819
Keywords: 330; Mikrofinanzierung; Agrarkredit; Ländliche Entwicklungsfinanzierung; Landwirtschaftsbank; Armutspolitik; Uganda